INDUCED SPAWNING OF LABEO DYOCHEILUS IN CAPTIVITY UNDER COLDWATER CONDITIONS - PANDEY, N. N.; HALDAR, R. S.; ALI, S.; KUMAR, P.; PATIYAL, R. S.; MAHANTA, P. C. (Journal of the Inland Fisheries Society of India, 2021)
An attempt was made to breed an indigenous carp, Labeo dyocheilus (McClelland) in captivity under coldwater condition at 18-22 o C temperature with optimization of synthetic hormone dose. Full maturity was observed during the 3rd week of July to the end of August. Hormone dose of 0.6 ml kg-1body for females and 0.3 ml kg-1 body for males was found optimum for spawning with 84-98% fertilization and high rate of hatching. Successful breeding of this species in captive condition enabled to produce seeds for wild stock augmentation and species diversification in coldwater aquaculture. Key words : Labeo dyocheilus, breeding, ovaprim, coldwater.